Improving Linguistics Skill on EFL Students Using Learning Management System: A Critical Literature Review - Triana, Yunika (Journal of Ethnic and Cultural Studies, 2025)
This research aimed to present a systematic review of articles discussing the implementation of a Learning Management System (LMS) for English as a Foreign Language (EFL) students and providing recommendations for English Language Teaching (ELT) through LMS in higher education institutions. The approach used was a systematic literature review that applies selection criteria to articles published in reputable international journals indexed in Scopus. The articles were selected either from publications between 2020 and 2022 or during the transition period from the COVID-19 pandemic to the post-pandemic era. The findings of the study indicated that online learning based on LMS offered significant benefits to both students and lecturers. Nevertheless, the implementation of LMS also brought forth several challenges that need to be addressed by institutions, lecturers, and students. The implications of this research have an impact on students’ learning experiences and the reinforcement of pedagogical competence among lecturers. Furthermore, these findings contribute to institutional proficiency in managing the learning process efficiently and responsibly, positioning it as an emerging trend in modern education.